Diagnostic laparoscopy in acute abdominal pain - Subramaniam, Ravichandran (International Surgery Journal, 2019)
Background: Acute Abdominal pain is an important surgical problem in all age groups. Early diagnosis is needed to rule out life threatening conditions. Diagnostic laparoscopy is a modern useful tool in giving proper treatment for all needed individuals. The aim of the present endeavor is to study the use of laparoscope in patients with acute pain over the abdomen, to diagnose and confirm conditions like acute appendicitis, appendicular abscess, doudenal perforation, ileal perforation. Ovarian torsion. mass formation, etc. where clinical and imaging studies are inconclusive. Methods: This study was conducted in the tertiary care hospital and the Department of General Surgery, Melmaruvathur Adhiparasakthi Institute of Medical Science and Research, Melmaruvathur. The period of study was from June 2017 to May 2018. All patients coming to the hospital with acute abdominal pain in the age group of ten years to seventy years were included in this study. Results: Majority of the patients had the findings relevant to the correct clinical diagnosis. However significant number of patients had unexpected findings and so the diagnosis was changed, and treatment also changed. Total 100 patients were included in this prospective study. 79 patients were found to have acute appendicitis. Duodenal perforation seen in 7 patients. Jejunal perforation seen in 2 patients. Mesenteric ischemia seen in 1 patient. Acute cholecystitis seen in 3 patients. Gall bladder perforation seen in 1 patient. Ectopic pregnancy was seen in 2 patients. Ovarian torsion seen in 3 patients. Ileocecal tuberculosis seen in 1 patient. No abnormality seen in 1 patient. Conclusions: The best approach in abdominal pain is to do diagnostic laparoscopy and proceed, rather than going for open laparotomy. Diagnostic laparoscopy gives all benefits of minimal invasive surgery. Not much of pain, shorter period of hospitalization, small scars, low infection rates and most importantly, accurate diagnosis and the correct treatment of most of the intra-abdominal conditions are the gifted things.